Viruses Infecting a Freshwater Filamentous Cyanobacterium ( Nostoc sp.) Encode a Functional CRISPR Array and a Proteobacterial DNA Polymerase B - Chénard, Caroline; Wirth, Jennifer F.; Suttle, Curtis A. (mBio, 2016)
Here we present the first genomic characterization of viruses infecting Nostoc , a genus of ecologically important cyanobacteria that are widespread in freshwater. Cyanophages A-1 and N-1 were isolated in the 1970s and infect Nostoc sp. strain PCC 7210 but remained genomically uncharacterized. Their 68,304- and 64,960-bp genomes are strikingly different from those of other sequenced cyanophages. Many putative genes that code for proteins with known functions are similar to those found in filamentous cyanobacteria, showing a long evolutionary history in their host. Cyanophage N-1 encodes a CRISPR array that is transcribed during infection and is similar to the DR5 family of CRISPRs commonly found in cyanobacteria. The presence of a host-related CRISPR array in a cyanophage suggests that the phage can transfer the CRISPR among related cyanobacteria and thereby provide resistance to infection with competing phages. Both viruses also encode a distinct DNA polymerase B that is closely related to those found in plasmids of Cyanothece sp. strain PCC 7424, Nostoc sp. strain PCC 7120, and Anabaena variabilis ATCC 29413. These polymerases form a distinct evolutionary group that is more closely related to DNA polymerases of proteobacteria than to those of other viruses. This suggests that the polymerase was acquired from a proteobacterium by an ancestral virus and transferred to the cyanobacterial plasmid. Many other open reading frames are similar to a prophage-like element in the genome of Nostoc sp. strain PCC 7524. The Nostoc cyanophages reveal a history of gene transfers between filamentous cyanobacteria and their viruses that have helped to forge the evolutionary trajectory of this previously unrecognized group of phages. IMPORTANCE Filamentous cyanobacteria belonging to the genus Nostoc are widespread and ecologically important in freshwater, yet little is known about the genomic content of their viruses. Here we report the first genomic analysis of cyanophages infecting filamentous freshwater cyanobacteria, revealing that their gene content is unlike that of other cyanophages. In addition to sharing many gene homologues with freshwater cyanobacteria, cyanophage N-1 encodes a CRISPR array and expresses it upon infection. Also, both viruses contain a DNA polymerase B-encoding gene with high similarity to genes found in proteobacterial plasmids of filamentous cyanobacteria. The observation that phages can acquire CRISPRs from their hosts suggests that phages can also move them among hosts, thereby conferring resistance to competing phages. The presence in these cyanophages of CRISPR and DNA polymerase B sequences, as well as a suite of other host-related genes, illustrates the long and complex evolutionary history of these viruses and their hosts. Filamentous cyanobacteria belonging to the genus Nostoc are widespread and ecologically important in freshwater, yet little is known about the genomic content of their viruses. Here we report the first genomic analysis of cyanophages infecting filamentous freshwater cyanobacteria, revealing that their gene content is unlike that of other cyanophages. In addition to sharing many gene homologues with freshwater cyanobacteria, cyanophage N-1 encodes a CRISPR array and expresses it upon infection. Also, both viruses contain a DNA polymerase B-encoding gene with high similarity to genes found in proteobacterial plasmids of filamentous cyanobacteria. The observation that phages can acquire CRISPRs from their hosts suggests that phages can also move them among hosts, thereby conferring resistance to competing phages. The presence in these cyanophages of CRISPR and DNA polymerase B sequences, as well as a suite of other host-related genes, illustrates the long and complex evolutionary history of these viruses and their hosts.